Isoelectronic and isolobal O, CH2, CH3+ and BH3 as electron pairs; similarities between molecular and solid‐state chemistry. Issue 2 (26th February 2016) - Vegas, Ángel; Notario, Rafael; Chamorro, Eduardo; Pérez, Patricia; Liebman, Joel F.
Abstract : A topological analysis of the electron localization function (ELF) of a molecule of hexamethyldisiloxane, (H3 C)3 –Si–O–Si–(CH3 )3, has been carried out, drawing a consistent picture of Si—O—Si bonding both in the linear and angular geometries. The ELF analysis confirms the idea that the O atom, in the linear geometry of (H3 C)3 —Si—O—Si—(CH3 )3, is isolobal with the isoelectronic —CH — and —BH3 — groups, the bonding in the Si—O—Si group being described as a two‐electron, three‐center (2 e, 3 c ) bond. At the same time, the three oxygen lone pairs mirror the three C—H and B—H bonds, respectively. On the contrary, in the angular geometry the same O atoms form two Si—O bonds and its lone pairs mimic the geometry of the —CH2 — group. In this model the O atoms would play the same role as the formally present O 2− anions in the `so‐called' ionic solids, such as in the skeletons of aluminate and silicate polyanions, thereby connecting molecular and solid‐state chemistry as formulated by the `fragment formalism' or the `molecular unit‐cell approach'. This unifying concept as well as the calculations we have carried out fully agree and also give support to earlier ideas developed by Bragg and Bent, among other authors. Bonding in the series of compounds P4, P4 O6, P4 O10, N4 (CH2 )6 (hexamethylenetetramine) and (CH)4 (CH2 )6 (adamantane) is discussed in the context of the isolobal model.